2010
DOI: 10.1016/j.virol.2010.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A Y-shaped RNA structure in the 3′ untranslated region together with the trans-activator and core promoter of Red clover necrotic mosaic virus RNA2 is required for its negative-strand RNA synthesis

Abstract: Red clover necrotic mosaic virus (RCNMV) is a positive-strand RNA virus with a bipartite genome. RNA1 encodes N-terminally overlapping replication proteins, p27 and p88. RNA2 is replicated efficiently by the replication proteins supplied in trans, whereas RNA1 needs p88 preferentially in cis for its replication. cis-Acting elements required for RNA2 replication have been mapped to the 3' terminal stem-loop structure conserved between RNA1 and RNA2, and to the protein-coding region including the trans-activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
(40 reference statements)
3
20
0
Order By: Relevance
“…Northern blot analysis confirmed the requirement of p27-YRE interaction for the negative-strand synthesis of RNA2 (Fig. 8A) (1,21,27). Western blot analysis in combination with BN-PAGE showed that the accumulation of the 480-kDa complex was increased by the addition of wild-type RNA2, whereas little increase in the accumulation of the 480-kDa complex was observed when RNA2 LM8 was added (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Northern blot analysis confirmed the requirement of p27-YRE interaction for the negative-strand synthesis of RNA2 (Fig. 8A) (1,21,27). Western blot analysis in combination with BN-PAGE showed that the accumulation of the 480-kDa complex was increased by the addition of wild-type RNA2, whereas little increase in the accumulation of the 480-kDa complex was observed when RNA2 LM8 was added (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Both p27 and p88 interact with RNA1 in a translation-coupled manner (27), and these interactions are important for the cis-preferential replication of RNA1 (66). p27 but not p88 binds specifically to the Y-shaped RNA element (YRE) of RNA2 in trans (27), and this interaction is essential for the recruitment of RNA2 into replication (1,21). In contrast, the functions of host proteins in RCNMV RNA replication are currently unknown.…”
mentioning
confidence: 99%
“…pET-His-MBP-p33, expressing p33 with dual 6ϫHis and maltose-binding protein (MBP) tags, was also obtained earlier (32). pMAL-MS 2 33, containing TBSV p33 fused in-frame with bacteriophage MS2 coat protein (MS2-CP), was obtained by PCR amplification of the MS2-CP open reading frame (ORF) from pGBK-MS2-CFP (20) using primers 1576 (5=-GGAGTCTAGAGCTTCTAACTTTACT CAG) and 3269 (5=-CCGCCATGGGTAGATGCCGGAGTTTGC) containing XbaI and NcoI restriction sites. The TBSV p33 ORF was amplified from pMAL92 using primers 3313 (5=-CGGACCATGGGAGACCATCA AGAGAATG) and 2744 (5=-CGGCTGCAGCTATTTGACACCCAGG GAC) containing NcoI and PstI restriction sites, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…pGBK-His33 and pGAD-His92, expressing only 6ϫHis-tagged p33 and p92, respectively, from the ADH1 promoter and pYC-DI72, were described previously (23). pGBK-Cup-(MS2) 2 -33 was obtained by fusing the CNV p33 ORF in frame with two copies of bacteriophage MS2-CP [(MS2) 2 , representing direct repeats of the MS2-CP ORF linked with a short linker (GAPGIHPGM) and also containing an internal poly-His tag]. The sequence of (MS2) 2 was amplified from p(MS2) 2 PCBP2 (39) using primers 4194 (5=-CGGACCATGGC GGATATCGAAGGTCCCACC) and 4196 (5= CCAGCCATGGGTCGTT TGGGTGATGGTGATGGTGGTGGCTGCCGCGTGG) containing an NcoI restriction site and cloned into NcoI-digested and dephosphorylated vector pGBK-His33/Cup1 (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation